A catalytic chemodosimetric approach for detection of nanomolar cyanide ions in water, blood serum and live cell imaging. Issue 45 (25th September 2015) - Kumar, Rahul; Sandhu, Sana; Hundal, Geeta; Singh, Prabhpreet; Walia, Amandeep; Vanita, Vanita; Kumar, Subodh
Abstract : The nano-molar detection of cyanide in live cell imaging and blood serum has been achieved through cyanide catalysed fluorescence enhancement with a TON between 70 and 360. Abstract : Naphthimidazolium based monocationic chemodosimetersCD-1 andCD-2 undergo cyanide mediated catalytic transformation in the presence of cyanide ions (0.01% to 1% ofCD-1 /CD-2 concentrations) with a turnover number from 70 to 360. These chemodosimeters can detect as low as 0.5 nM and 1 nM cyanide ions under nearly physiological conditions (HEPES buffer–DMSO (5%), pH 7.4). The structures ofCD-1 and its cyanide induced hydrolyzed product4 have been confirmed by single crystal X-ray crystallography.CD-1 can also be used for the determination of 2 nM cyanide in the presence of blood serum.CD-1 andCD-2 also find applications in live cell imaging of 10 nM cyanide ions in rat brain C6 glioma cells. To the best of our knowledge, this is the first report where high sensitivity towards cyanide ions has been achieved through catalytic hydrolysis of the fluorescent chemodosimeter.